2018
DOI: 10.3892/ol.2018.9838
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑543 suppresses liver cancer growth and induces apoptosis via the JAK2/STAT3 signaling pathway

Abstract: The aim of the present study was to investigate the function of microRNA-543 on liver cancer cell proliferation and apoptosis, and also to identify whether the Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) signaling pathway was a direct target of microRNA-543. When compared with paracarcinoma tissue, microRNA-543 expression in tissue samples from patients with liver cancer was identified to be decreased. Furthermore, overall survival of patients with high microRNA-543 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The basal level of miR-543 in chemoresistant CRC cells was significantly higher than that in chemosensitive CRC cells (Figure 2C). Although several studies have revealed that miR-543 acts as an oncogene in various cancers 17-19, miR-543 has been reported to function as a tumor suppressor 20-22 . To validate the roles of miR-543 in the chemosensitivity of L-OHP, miR-543 was overexpressed in HCT116 and HCT-8 cells by directly transfecting cells with a miR-543 mimic or infecting cells with the overexpression virus.…”
Section: Resultsmentioning
confidence: 99%
“…The basal level of miR-543 in chemoresistant CRC cells was significantly higher than that in chemosensitive CRC cells (Figure 2C). Although several studies have revealed that miR-543 acts as an oncogene in various cancers 17-19, miR-543 has been reported to function as a tumor suppressor 20-22 . To validate the roles of miR-543 in the chemosensitivity of L-OHP, miR-543 was overexpressed in HCT116 and HCT-8 cells by directly transfecting cells with a miR-543 mimic or infecting cells with the overexpression virus.…”
Section: Resultsmentioning
confidence: 99%
“…However, Fan et al (2016) found that miR‐543 expression was downregulated in CRC tissue samples and had a tumor‐suppressive effect. L. P. Liu, Yang, et al (2017) and Xiu, Wang, Wang, Ji, and Zhang (2019) confirmed the low expression of miR‐543 in tissue samples of hepatocellular carcinoma (HCC), while Visalli et al (2018) found upregulation of miR‐543 expression in tissue samples from patients with HCC. Dang, Zheng, Liu, Wu, and Wu (2017) found that the expression level of miR‐543 was upregulated in cervical cancer tissue, while X. Liu, Gan, and Zhang (2019) and Ma et al (2020) found that miR‐543 expression was downregulated in cervical cancer tissue and cells.…”
Section: The Role Of Mir‐543 In Human Cancermentioning
confidence: 97%
“…L. P Liu, Yang, et al (2017). andXiu, Wang, Wang, Ji, and Zhang (2019) confirmed the low expression of miR-543 in tissue samples of hepatocellular carcinoma (HCC), whileVisalli et al (2018) found upregulation of miR-543 expression in tissue samples from patients with HCC Dang, Zheng, Liu, Wu, and Wu (2017). found that the expression level of miR-543 was upregulated in cervical cancer tissue, while X Liu, Gan, and Zhang (2019).…”
mentioning
confidence: 88%
“…Inhibition of miRNA-543 expression resulted in liver cancer cells with exactly the same consequences like inhibition of miRNA-409: increased cancer cell proliferation and decreased apoptosis. It also activated the protein expression of phosphorylated JAK2, phosphorylated STAT3, c-Myc, and B-cell lymphoma 2 (Bcl-2) in liver cancer cells [53]. miRNA-3662, which downregulated in HCC tissues and cell lines, may be involved in reprogramming cancer cells' glucose metabolism and forming of Warburg effect while having hypoxia-inducible factor-1α (HIF-1α) as one of the direct targets.…”
Section: Mirna Expression Patterns In Hccmentioning
confidence: 99%